Research handbook of fiduciary law - Smith, D. Gordon, 1962-; Gold, Andrew S., 1973- (Research handbooks in corporate law and governance, 2018)
Fiduciary duties are widely viewed as essential to myriad private relationships, including guardianships, employment relationships, trusts, business organizations, and professional relationships. Recently, legal scholars and courts have devoted increasing attention to the application of fiduciary principles to public officials and public institutions. Some have argued that fiduciary relationships are unified by a common structure, but courts and commentators typically treat each fiduciary relationship as distinct. As a result, fiduciary law is often viewed as fragmented. The Research Handbook on Fiduciary Law shows that fiduciary law can be a distinctive field of study in its own right. This timely work presents important accounts of fiduciary relationships and new ideas on how fiduciary law can be explained. Coverage includes discussion of fiduciary obligations, fiduciary remedies, the role of equity and trusts, and public fiduciary law. A number of comparative perspectives are introduced to highlight similarities and differences between leading jurisdictions. The chapters in this Research Handbook help to show why this subject has drawn so many distinctive points of view, and sheds new light on a multi-faceted and rapidly growing field of study. This Research Handbook will be of interest to readers concerned with both the theory and practice of fiduciary law, as it incorporates significant new insights and developments in the field. It will also act as a starting point of new inquiry for those looking to contribute to the field themselves.